A Study on Cabbage (Brassica oleracea)Peroxidase Activityusing three medicinal plant leaf extracts - Sharma, Nikita; Sravani, M.; Padma, S. (International Journal of Scientific Research in Biological Sciences, 2019)
Peroxidases are a group of antioxidant enzymes which are widely distributed in nature and have been important both in plants and animals for variousphysiological processes. These enzymes utilize a wide variety of substrates to bring about the redox reactions. In the present study, peroxidase was partially purified from cabbage. In view of the diverse roles catalyzed by this enzyme, it was of interest to identify novel regulators of enzyme activity. Thus the activity of the enzyme was assayed in the presence and absence of three medicinal plant leaf extracts of Azadirachta indica(Neem), Ocimum tenuiflorum (Tulsi).and Murraya koenigii (Curry Leaves). These three leaf extracts are known for their medicinal properties and have been used in treating chronic diseases. Studies conducted revealed that all the plant leaf extracts inhibited the activity of peroxidase to a significant extent. Further studies need to be conducted to ascertain the significance of peroxidase inhibition